The significance of consciousness - Siewert, Charles P., 1959- (Princeton, N.J. : Princeton University Press, 1998)
Charles Siewert presents a distinctive approach to consciousness that emphasizes our first-person knowledge of experience and argues that we should grant consciousness, understood in this way, a central place in our conception of mind and intentionality. Written in an engaging manner that makes its recently controversial topic accessible to the thoughtful general reader, this book challenges theories that equate consciousness with a functional role or with the mere availability of sensory information to cognitive capacities
Visual experience: intentionality and richness. Can we take the intentional out of the phenomenal? ; Framing the issue ; Is the phenomenal holistic enough to be intentional? ; Sense-data inflated (and exploded) ; Sensory intentionality is not bestowed by judgment ; Might essential environmental and behavioral links be missing? ; The intentionality of color experience ; Visual experience: untold riches ; Other forms of phenomenal visual wealth ; Summary. -- Conscious thought. Conscious thought -- iconic and noniconic ; Intentionality and visualization ; Consciousness thought: not just imagery ; The relation of phenomenal and intentional differences in thought ; Thought's seeming: inseparable from thought ; Conclusion. -- The importance of consciousness. Does consciousness matter? ; Experience for its own sake ; The importance of being conscious ; Should we care so much about consciousness? ; But must we talk about it? ; Conclusion
Includes bibliographical references (pages 365-368) and index
Keywords: Consciousness; Consciousness